A review of multiple sclerosis with Asian perspective - Chong, H.T.; Tan, Chong Tin (Malaysian Medical Association, 2008)
Multiple sclerosis, although a rare disease in Asia, often presents significant diagnostic challenges to clinicians. There has been rapid advancement in the understanding of the underlying genetic influence, pathophysiology, investigation and treatment recently. This paper reviewed the latest development of various aspects of the disease and examined the differences between the manifestations of Asian and Western patients. The implications of these differences to investigation and treatment were also touched upon.